Wild, scenic, and toxic: Recent degradation of an iconic Arctic watershed with permafrost thaw - Patrick F. Sullivan; Roman J. Dial; David J. Cooper; Charles Diamond; Christopher J. Tino; Daniel D. Gregory; Russell E. Wong; Timothy W. Lyons (Proceedings of the National Academy of Sciences, 2025)
The streams of Alaska’s Brooks Range lie within a vast (~14M ha) tract of protected wilderness and have long supported both resident and anadromous fish. However, dozens of historically clear streams have recently turned orange and turbid. Thawing permafrost is thought to have exposed sulfide minerals to weathering, delivering iron and other potentially toxic metals to aquatic ecosystems. Here, we report stream water metal concentrations throughout the federally designated Wild and Scenic Salmon River watershed and compare them with United States Environmental Protection Agency (EPA) chronic (4-d) exposure thresholds for toxicity to aquatic life. The main stem of the Salmon had elevated SO 4 2− concentrations and elevated SO 4 2− : Ca relative to a predisturbance baseline for most of its length, consistent with increased sulfide mineral weathering. Most of the tributaries also had elevated SO 4 2− concentrations and elevated SO 4 2− : Ca, especially those in the upper watershed. The Salmon River mainstem consistently exceeded EPA chronic exposure thresholds for total recoverable iron, total recoverable aluminum, and dissolved cadmium from its first major tributary to its mouth. Nine of ten major tributaries that we sampled exceeded EPA thresholds for at least one metal on at least one of three sampling dates. Our findings indicate that habitat quality for resident and anadromous fish has been severely degraded in the Salmon River watershed. Loss of important spawning habitat in the Salmon and many other streams in the region might help explain a recent crash in chum salmon returns, which local communities depend upon for commercial and subsistence harvest.